2014
DOI: 10.1530/jme-14-0127
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant miR199a-5p/caveolin1/PPARα axis in hepatic steatosis

Abstract: The prevalence of non-alcoholic fatty liver disease (NAFLD), a condition characterized by an excessive accumulation of triglycerides (TGs) in hepatocytes, has dramatically increased globally during recent decades. MicroRNAs (miRs) have been suggested to play crucial roles in many complex diseases and lipid metabolism. Our results indicated that miR199a-5p was remarkably upregulated in free fatty acid (FA)-treated hepatocytes. To investigate the role of miR199a-5p in the pathogenesis of fatty liver and the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…Similar results have been observed in a previous study that demonstrated that the downregulated expression of OA/PA induced steatosis in hepatocytes and livers from HFD mice, db/db mice and ob/ob mice, and NAFLD patients [18]. One study reported a major decrease in CAV1 expression in the visceral adipose tissue of obese patients [9].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results have been observed in a previous study that demonstrated that the downregulated expression of OA/PA induced steatosis in hepatocytes and livers from HFD mice, db/db mice and ob/ob mice, and NAFLD patients [18]. One study reported a major decrease in CAV1 expression in the visceral adipose tissue of obese patients [9].…”
Section: Discussionsupporting
confidence: 89%
“…miR-1 is associated with fatty acid uptake in cardiomyocytes by negatively regulating the expression of heart-type fatty acid binding protein 3 (FABP3) [67]. miR-199a participated in mitochondrial activity by inhibiting the expression of mitochondrial fatty acid β-oxidation related genes through CAV1 suppression [68]. In cultured myocytes, overexpression of miR-696 resulted in decreased fatty acid oxidation compared with normal control myocytes, through direct targeting PGC-1α [69].…”
Section: The Role Of Mirnas In Cardiac Metabolic Homeostasismentioning
confidence: 99%
“…It has been shown that miR-27a regulates lipid metabolism by targeting the lipid synthetic RXRα and the lipid transporter ATP-binding cassette subfamily A1 in addition in regulating several lipid metabolismrelated genes which play a crucial role in the production of infectious viral particles 47. Upregulation of miR-199a-5p impaired fibrillar Aβ-oxidation via inhibition of caveolin 1 (CAV1) and the PPARα pathway which refers to its vial role in the development of NAFLD 48. The positive correlation between declining of miR-27a/miR-93 and elevation of miR-199 with the severity of hepatic steatosis in CHC patient in the current study suggest their attractive therapeutic targets for NAFLD.5 | CONCLUSIONOur data indicated that serum miRNAs might be useful biomarkers for prediction of CHC (miR-21, miR-23b, miR-27a, miR-106, and miR-122) and liver disease progression (miR-27a, miR-93, and miR-199) in addition to their attractive therapeutic targets.…”
mentioning
confidence: 99%